The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3390/vaccines8010035
|View full text |Cite
|
Sign up to set email alerts
|

Cytomegalovirus and Epstein–Barr Virus Associations with Neurological Diseases and the Need for Vaccine Development

Abstract: Herpesviruses have been isolated from a wide range of hosts including humans—for which, nine species have been designated. The human herpesviruses are highly host adapted and possess the capacity for latency, allowing them to survive in the host for life, effectively hidden from the immune system. This ability of human herpesviruses to modulate the host immune response poses particular challenges for vaccine development but at the same time proves attractive for the application of human herpesvirus vaccines to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 129 publications
(118 reference statements)
0
12
0
Order By: Relevance
“…The life cycle of EBV is particularly complex and the virus undergoes the latency phase during which it expresses several genes impacting oncogenesis [44][45][46][47]. Recent studies have shown that EBV DNA is present in large quantities in patients with autoimmune diseases of several etiologies [48,49]. However, there are no proofs on the effect of EBV reactivation on the expression of PD-1 and PD-L1 antigens in patients with primary GN.…”
Section: Discussionmentioning
confidence: 99%
“…The life cycle of EBV is particularly complex and the virus undergoes the latency phase during which it expresses several genes impacting oncogenesis [44][45][46][47]. Recent studies have shown that EBV DNA is present in large quantities in patients with autoimmune diseases of several etiologies [48,49]. However, there are no proofs on the effect of EBV reactivation on the expression of PD-1 and PD-L1 antigens in patients with primary GN.…”
Section: Discussionmentioning
confidence: 99%
“…The extensive use of these drugs in the therapy has formed the problem of drug resistance, leading to noticeable treatment failure [ 32 , 33 , 34 ]. While various ongoing studies have attempted to produce herpesvirus vaccination, no vaccines or antiviral drugs have been approved for the prevention of herpesvirus infections so far [ 35 , 36 ]. Therefore, there is an urgent demand for developing novel antiherpetic drugs that could effectively cure or prevent herpesvirus infections with less resistance, diminished adverse effects, low toxicity, and improved stability [ 37 , 38 ].…”
Section: Anti-herpesvirus Drugs Used In Clinicsmentioning
confidence: 99%
“…Moreover, several studies have shown that HCMV infection causes the occurrence and progression of several chronic diseases, including autoimmune disease (AID) [ 33 ], tuberculosis [ 34 ], atherosclerosis [ 7 ], mental disorders [ 35 ], age-related macular degeneration (AMD) [ 36 ], pneumonitis, and myocarditis [ 37 ]. In particular, many studies have revealed that HCMV infection is related to various cancers, such as cervical cancer [ 38 ], breast cancer [ 39 ], colorectal cancer [ 40 ], ovarian cancer [ 41 ], prostate cancer [ 42 ], squamous cell carcinoma [ 43 ], lymphoma [ 44 ], glioblastoma [ 45 ], medulloblastoma [ 46 ], and neuroblastoma [ 47 ], as well as poor outcomes. A list of HCMV-related diseases is provided in Figure 1 .…”
Section: The Prevalence and Perniciousness Of Hcmvmentioning
confidence: 99%